Herbal dry extract BNO 1011 improves clinical and mucociliary parameters in a rabbit model of chronic rhinosinusitis. Issue 6 (18th January 2019) - Cho, Do‐Yeon; Skinner, Daniel; Mackey, Calvin; Lampkin, Harold B; Elder, Jeffrey Brent; Lim, Dong Jin; Zhang, Shaoyan; McCormick, Justin; Tearney, Guillermo J.; Rowe, Steven M.; Woodworth, Bradford A.
Abstract : Background: Enhancing chloride (Cl – ) secretion in sinus epithelia represents a novel therapeutic approach to chronic rhinosinusitis (CRS). Herbal dry extract BNO 1011 enhances mucociliary clearance (MCC) via upregulation of Cl – secretion in sinonasal cultures in vitro and murine epithelium in vivo. The objective of this study is to evaluate whether the BNO 1011 improves MCC and clinical parameters in a rabbit model of CRS. Methods: After the development of CRS in 30 New Zealand white rabbits, animals were randomly assigned to receive oral placebo (n = 10), BNO 1011 (low dose [LD], 25 mg/kg/daily) (n = 10), or BNO1011 (high dose [HD], 125 mg/kg/daily) (n = 10) for 4 weeks. Outcomes included sinus opacification (Kerschner's rabbit sinus CT grade), maxillary epithelial Cl − secretion (sinus potential difference [PD] assay), airway surface liquid (ASL) depth using micro‐optical coherence tomography (μOCT), and submucosal gland density (SMD) on histopathology. Outcome parameters were analyzed by 2 blinded investigators. Results: BNO 1011 significantly cleared sinus opacification (HD = 1.21 ± 0.63, LD = 1.26 ± 0.37, ) compared to placebo (4.02 ± 0.92) ( p = 0.009). BNO 1011 resulted in markedly greater mean sinus PD polarization (HD = –12.23 ± 1.4 mV, LD = –12.0 ± 3.0 mV) when compared to rabbits treated with placebo (–4.1 ± 1.1 mV) ( p = 0.03). ASL depth was significantly improved when treated with HD (4.08 ± 0.06 μm) and LD (4.05 ± 0.06 μm) compared to placebo (3.5 ± 0.05 μm) (post hoc analysis, p < 0.0001). Histologically, epithelial thickness (HD = 10.0 ± 0.7 μm; LD = 13.7 ± 0.9 μm; placebo = 21.1 ± 2.3 μm; p < 0.005), subepithelial thickness (HD = 63.1 ± 6.6 μm; LD = 103.2 ± 6.7 μm; placebo = 113.3 ± 6.0 μm; p < 0.001), and SMD (HD = 22.2 ± 2.9%; LD = 31.8 ± 1.1%; placebo = 43.8 ± 1.7%; p < 0.0001) were noticeably better with the HD. Conclusion: Herbal dry extract BNO 1011 improves radiographic, histologic, and MCC parameters in a rabbit model of CRS.